Do major customers promote firms' innovation? - Jinsong Tan; Huijuan Cao; Xiangting Kong (China Journal of Accounting Research, 2019)
This study examines whether and how a concentrated supply chain relationship affects a firm's innovation decisions. Using data from Chinese listed firms in the manufacturing industry, we find that a concentrated customer base constrains a firm's R&D investment, where a 1% increase in customer concentration is associated with a 0.011% decrease in R&D investment. To establish causality, we use the instrumental variable method, the reverse causality model, and the Granger causality test to re-examine the relationship and arrive at a consistent conclusion. Results from mechanism analysis suggest that a concentrated customer base constrains the internal fund availability and that the negative relationship between customer concentration and firms' innovation is less pronounced for firms with more external financial support. Additional analysis reveals that the negative effect of customer concentration mainly affects R&D investment expenditure and that customer concentration also constrains innovation output in China. Overall, our paper reveals the dark side of close customer-supplier relationships and provides new insights into how supply chain relationships affect firms' innovation decisions.
Keywords: 650; Customer concentration; Financial constraint; Innovation; Supply chain